Caracterização morfológica, molecular e patogênica de isolados de colletotrichum spp. de mangueira e a atividade inibitória de óleos essenciais sobre este patógeno - Silva Neto, Jorge Alves (Universidade Federal Rural do Semi-Árido, 2020)
The mango tree (Mangifera indica L.) stands out as one of the most important tropical fruit trees in the world. Anthracnose, caused by phytopathogenic fungi of the genus Colletotrichum, is a disease mainly related to post-harvest periods, directly affecting this crop. Therefore, this study aimed at the morphological, molecular and pathogenic characterization of Colletotrichum spp. of hoses and the inhibitory activity of essential oils on this pathogen. Fungal discs of 5 mm were placed in Petri dishes to evaluate the growth speed and colony color. Microcultures were carried out to analyze the shapes and dimensions of conidia and appressoria. For molecular analysis, the isolates were previously identified with primers specific gene of gender and species for C. gloeosporioides. Nine ISSR markers (Inter Simple Sequence Repeats) and 12 RAPD markers (Random Amplified Polymorphic DNA) were used to identify the genetic diversity of the 28 isolates. In the morphological evaluation, from the found structures, colony color, conidia, appressoria and growth rate, 28 isolates were identified belonging to the species C. gloeosporioides and later confirmed with specific primers genes. The RAPD and ISSR markers were considered satisfactory in detecting genetic diversity. The combination of the markers generated a variation of similarity from 0.23 (between isolates 12 and 21) to 0.71 (between isolates 2 and 4), thereby identifying high level of variability among fungi, where the dissimilarity was higher to 75%. The generated dendogram revealed the formation of 8 main groups. There were no genetic clusters correlated with the collection site, thus demonstrating the great genetic diversity even among individuals from the same location. The pathogenicity of C. gloeosporioides isolates was evaluated in Tommy Atkins mango fruits by introducing 7 mm mycelial discs. For the in vitro test, three more pathogenic isolates were used to assess inhibition with the oils of ginger (Zingiber officinale), dragon blood (Croton Lenchleri) and the combination of both at concentrations of 0.2; 0.4; 0.6 and 0.8%. The same treatments were used for the in vivo test. After the introduction of mycelial discs in mango fruits, the different concentrations of oils were spread on the inoculated surface and maintained during seven days after the evaluation. Based on the pathogenicity test, most isolates showed low virulence in the cultivar Tommy Atkins. However, some isolates have been shown to be highly pathogenic to this cultivar. In in vitro tests, there were significant differences between treatments, with the highest mean inhibition being 28.5% found in the combination of 0.3% ginger plus 0.3% dragon blood. For in vivo tests, all treatments were highly effective in Tommy mango, with 100% inhibition of fungal growth in the fruit. The data generated in this work allow us to conclude that there is variation not only genetic, but also in the level of pathogenicity among isolates of C. gloeosporioides collected in commercial mango plantations and that not always single control measures can be sufficient or 100% effective in the fight this disease. The inhibiting effect of ginger oil and dragon blood on the evaluated isolates reveals that these can be an effective method of controlling anthracnose
Keywords: Fitopatógenos; Diversidade genética; Patogenicidade; Phytopathogens; Genetical diversity; Pathogeni; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA